Issues of Assessing the Reliability of the Evidence in the Formation of the Database of Verifications - Usanovich, Ganiev Zafar; Ravshanovich, Avazov Ilkhom (International Journal on Orange Technologies, 2022)
The scientific article provides the analytical information used in audit, the quality of audit organization's data and the financial position of the audited entity, as well as the conclusions, scientific recommendations on auditors' data processing.